Using surface-induced ordering to probe the isotropic-to-nematic transition for semiflexible polymers. Issue 28 (27th June 2016) - Zhang, Wenlin; Gomez, Enrique D.; Milner, Scott T.
Abstract : By progressively increasing backbone stiffness for chains between two impenetrable surfaces, we probe the isotropic-to-nematic phase transition for semiflexible polymers in simulations. Abstract : Semiflexible polymers undergo a weakly first order isotropic-to-nematic (IN) phase transition when the volume fraction ϕ is high enough that random alignment of the backbone segments is no longer viable. For semiflexible chains, the critical volume fraction ϕ c is governed by the backbone stiffness N p . To locate the IN phase transition, we perform molecular dynamics (MD) simulations of bead-spring chains confined between two impenetrable parallel surfaces. We use the impenetrable surfaces to induce nematic–isotropic interfaces for semiflexible chains in the isotropic phase. By progressively increasing the backbone stiffness N p, we observe the propagation of surface-induced nematic order above a critical stiffness N cp for a given ϕ . Using the simulation results N cp( ϕ ), we construct the IN phase boundry in the ϕ – N p plane, from which the scaling relation between ϕ c and N p is obtained. For semiflexible chains with N p ≤ 5.78, our results suggest ϕ c ∼ N p −1, consistent with prediction by Khokhlov and Semenov. For chains with N p ≥ 5.78, we observe a new scaling regime in which ϕ c ∼ N p −2/3 .